Hygiene assessment of essix retainers via a patient questionnaire - Kılınç, Delal Dara; Sayar, Gülşilay (My University, 2019)
Aim: The aim of this study was to investigate the hygiene habits and cleaning methods of patients who are wearing Essix plates for retention, by a face to face applied questionnaire. Material and Methods: 120 patients (72 females, 48 males) using Essix Plates in post-treatment retention period were enrolled for this study. Subjects were aged 18-40 years. All of the subjects were conducted a questionnaire by the same experienced clinician. The questionnaire investigated the genders of subjects, ages of subjects, and methods and frequency of cleaning plates. Results: Half of the subjects clean their plates whenever they remove it. There is a difference between median ages according to the frequency of clearing the plates (p <0.001). There is no difference between the ages about; how the plates are cleaned, what they use to clean, the difficulty in cleaning, and the belief about the plates are clean enough (p values are 0.833, 0.178, 0.120 and 0.251, respectively). The belief that plates are sufficiently clean does not differ according to sex (p = 0.871). According to age distribution, there was a statistically significant correlation the frequency of clearing the age groups and plates, the way of clearing the plates, the agent to be used to clean the plates and the belief of cleanliness of the plates (p <0.05). Conclusions: There is not a common method of cleaning the Essix plates amongst patients. Patients refer various materials to clean their Essix plates. The frequencies of cleaning their plates also differ amongst patients. Various hygiene habits were present in different age groups.

Amaç: Bu çalışmanın amacı ortodontik tedavi sonrası retansiyon döneminde Essix plak taşıyan hastaların hijyen alışkanlıklarının anketler aracılığı ile değerlendirilmesidir. Gereç ve Yöntem: Çalışmaya ortodontik tedavisi bitmiş ve retansiyon amacı ile Essix plak kullanan, 18-40 yaş aralığındaki 120 hasta (72 kadın, 48 erkek) dahil edilmiştir. Hastaların hepsine klinik tecrübesi olan aynı ortodontist tarafından anketler uygulanmıştır. Anket hastaların yaşlarını, cinsiyetlerini, hastaların plakları temizleme metodlarını ve sıklıklarını incelemiştir. Bulgular: Hastaların yarısı, plaklarını her çıkardıkarında temizlediklerini belirtmiştir. Plakları temizleme sıklığına göre hastaların ortalama yaşı arasında farklılık bulunmaktadır (p <0,001). Plakların nasıl temizlendiği, temizlemek için kullanılan ajan, temizlemede güçlük, plakların temizliği konusundaki görüş açısından ortalama yaşta farklılık yoktur (p değerleri sırasıyla 0,833, 0,178, 0,120 ve 0,25). Plakların temizliği ile ilgili düşünce cinsiyetten bağımsızdır (p =,.871). Yaş dağılımına göre plakların temizleme sıklığı, nasıl temizlendiği, kullanılan temizleme ajanı temizlik hakkında görüş arasında istatistiksel olarak anlamlı farklılık bulunmaktadır (p <0,05). Sonuç: Hastalar arasında Essix plaklarının temizlenmesi açısından çeşitlilik olduğu, hastaların plaklarını temizlemek için farklı materyaller tercih ettiği anlaşılmıştır.
Essix retansiyon apareylerinin hasta anketleri ile hijyen değerlendirmesi
Keywords: Orthodontic Retainer; Essix Plates; Hygiene; Disinfection; Ortodontik Pekiştirme Apareyleri; Essix Plaklar; Hijyen; Dezenfeksiyon